Effects of Bacillus subtilis or Lentilactobacillus buchneri on aerobic stability, and the microbial community in aerobic exposure of whole plant corn silage - Yin, Hang; Zhao, Meirong; Pan, Gang; Zhang, Hongyu; Yang, Rui; Sun, Juanjuan; Yu, Zhu; Bai, Chunsheng; Xue, Yanlin (Frontiers in Microbiology, 2023)
This study aimed to evaluate the effects of Bacillus subtilis or Lentilactobacillus buchneri on the fermentation quality, aerobic stability, and bacterial and fungal communities of whole plant corn silage during aerobic exposure. Whole plant corn was harvested at the wax maturity stage, which chopped to a length of approximately 1 cm, and treated with the following: distilled sterile water control, 2.0 × 105 CFU/g of Lentilactobacillus buchneri (LB) or 2.0 × 105 CFU/g of Bacillus subtilis (BS) for 42 d silage. Then, the samples were exposed to air (23-28 ℃) after opening and sampled at 0 h, 18 h and 60 h, to investigate fermentation quality, bacterial and fungal communities, and aerobic stability. Inoculation with LB or BS increased the pH value, acetic acid, and ammonia nitrogen content of silage (P < 0.05), but it was still far below the threshold of inferior silage, the yield of ethanol was reduced (P < 0.05), and satisfactory fermentation quality was achieved. With the extension of the aerobic exposure time, inoculation with LB or BS prolonged the aerobic stabilization time of silage, attenuated the trend of pH increase during aerobic exposure, and increased the residues of lactic acid and acetic acid. The bacterial and fungal alpha diversity indices gradually declined, and the relative abundance of Basidiomycota and Kazachastania gradually increased. The relative abundance of Weissella and unclassified_f_Enterobacteria was higher and the relative abundance of Kazachastania was lower after inoculation with BS compared to the CK group. According to the correlation analysis, Bacillus and Kazachastania are bacteria and fungi that are more closely related to aerobic spoilage and inoculation with LB or BS could inhibit spoilage. The FUNGuild predictive analysis indicated that the higher relative abundance of fungal parasite-undefined saprotroph in the LB or BS groups at AS2, may account for its good aerobic stability. In conclusion, silage inoculated with LB or BS had better fermentation quality and improved aerobic stability by effectively inhibiting the microorganisms that induce aerobic spoilage.